A Case Report of Subcutaneously Injected Liposomal Cannabidiol Formulation Used as a Compassion Therapy for Pain Management in a Dog - Shilo-Benjamini, Yael; Cern, Ahuva; Zilbersheid, Daniel; Hod, Atara; Lavy, Eran; Barasch, Dinorah; Barenholz, Yechezkel (Frontiers in Veterinary Science, 2022)
A 14-year-old intact mixed breed dog (26 kg) was submitted for a novel cannabidiol (CBD) analgesic treatment. The dog was cachectic and had a testicular neoplasia, hip and elbow osteoarthritis and severe cervical pain. The owners preferred not to continue with diagnostic tests of the cervical disease. Analgesic treatment included canine osteoarthritic supplement, robencoxib and gabapentin. An additional liposomal CBD injectable formulation at 5 mg/kg was administered subcutaneously between the shoulder blades. The dog was monitored using an activity monitoring collar (PetPace), owner wellbeing questionnaire, pain interactive visual analogue scale (iVAS), blood work and CBD plasma concentrations. A week from the injection and up to 3 weeks afterwards the dog had improved owner and iVAS pain scores, and increased collar activity scores. CBD was quantified in plasma for 28 days. Due to disease progression, further difficulty to rise and walk, and relapse to pain after 3 weeks, the owners requested a second liposomal CBD injection, which was performed 4 weeks following the first injection using 3 mg/kg dose. Two days later, the dog was found dead in the yard under direct sun, while environmental temperature was 37°C. Major findings on necropsy revealed evidence of heat stroke and severe cervical disc protrusion with spinal hematoma, none related to liposomal CBD. In conclusion, subcutaneous liposomal CBD produced quantifiable CBD plasma concentrations for 28 days and may be an effective additional treatment as part of multimodal pain management in dogs.